The Moderating Effect of Firm Size on The Influence of Ownership Structure on Earnings Management Practices - Reindivtia, Ida Ayu; Wirama, Dewa Gede (Yayasan Riset dan Pengembangan Intelektual, 2025)
Earnings management refers to the choice of accounting policies or real actions taken by manager to influence earnings in order to achieve specific reported earnings numbers. This study aims to examine the effect of ownership structure on earnings management practices and to analyze the role of firm size as a moderating variable. The theory employed in this study is agency theory. The research was conducted on all manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2021-2023. The sample was selected using a purposive sampling method, resulting in 52 companies that met the criteria, with a total of 156 observations. The data analysis technique used in this study is moderated regression analysis. The results show that institutional ownership, foreign ownership, and public ownership have negative effects on earnings management. Firm size weakens the negative effect of institutional ownership and public ownership on earnings management. However, firm size does not moderate the relationship between foreign ownership and earnings management. The findings of this study highlight the importance of ownership structure as an effective monitoring mechanism especially for larger firms. These results can serve as a consideration for stakeholders in enhancing corporate governance and monitoring effectiveness.